The enemy in the mirror: self-perception-induced stress results in dissociation of psychological and physiological responses in patients with dissociative disorder. (1st November 2018) - Schäflein, Eva; Sattel, Heribert; Schmidt, Ulrike; Sack, Martin
ABSTRACT: Background : Patients suffering from dissociative disorders (DD) are characterized by an avoidance of aversive stimuli. Clinical experience has shown that DD patients typically avoid the confrontation with their own faces in a mirror (CFM). Objective : To investigate potential CFM-associated self-reported and psychophysiological stress reactions of DD patients, which most likely inform on the still unknown pathophysiology of dysfunctional self-perception in DD. Method : Eighteen DD patients and 18 healthy controls (HCs) underwent CFM. They were assessed for CFM-induced subjective self-reported stress, acute dissociative symptoms and sympathetic and parasympathetic drive using impedance cardiography. Results : DD patients experienced more subjective stress and acute dissociation than HCs upon CFM. Their psychological stress response did not activate the sympathetic and parasympathetic nervous system. Conclusions : In DD patients, CFM constitutes serious self-reported stress and is associated with a blunted autonomic reactivity. Therapeutic approaches promoting self-perception and self-compassion, in particular by using CFM, might serve as goal-oriented diagnostic and therapeutic tools in DD.